Annealing effect on structural and optical properties of glad synthesized Gd2O3 nanorod - Ph. Nonglen Meitei; Naorem Khelchand Singh (Discover Materials, 2023)
Abstract Gadolinium oxide nanorod (Gd2O3 NR) was fabricated on an n-type silicon substrate by catalyst-free glancing angle deposition (GLAD) technique. The as-grown sample was annealed at 500 °C to investigate the impact of annealing on structure and optical properties. XRD analysis reveals an improvement in the crystal structure after annealing. Field emission scanning electron microscope (FE-SEM) and energy dispersive X-ray (EDX) confirm the successful growth of vertically aligned Gd2O3 NR with the presence of Gd, O, and Si. Transmission electron microscope (TEM) showed the crystalline nature of the grown Gd2O3 NR. Finally, UV–vis spectroscopy was performed to study the optical properties. A significant enhancement in the photon absorption (200–300 nm) was observed, which can be attributed to increased grain size, improved crystallinity, and large generation of electron–hole pairs. In addition, the Tauc plot showed a decrease in the bandgap from 5.05 eV to 4.98 eV after annealing at 500 °C.